The Influence of Site Class and Code Evolution on the Seismic Performance of a Four-Story Building - Rabbani Nauval (E3S Web of Conferences)
The safety, performance, and sustainability of buildings are crucial, especially in seismically active regions. This study evaluates the seismic performance of a four-story office building designed under Indonesian seismic codes from 2002, 2012, and 2019. Using finite element modeling, the analysis incorporates variations in site classes to assess the structural and seismic response systematically. The results demonstrate significant differences in structural response across the three seismic codes and site classes. Buildings designed under the 2002 code exhibit higher seismic vulnerability than those designed using the 2012 and 2019 codes, particularly regarding story drift and base reactions. These findings highlight the progressive improvement in seismic safety achieved through code updates and the critical role of site-specific considerations in structural performance. Furthermore, the study underscores the importance of adopting modern seismic standards in supporting sustainable infrastructure development. By reducing reconstruction needs, optimizing material use, and improving long-term resilience, these standards contribute to safer and more sustainable urban environments. This research offers valuable insights for engineers and policymakers, emphasizing the importance of seismic code evolution in ensuring resilience and sustainability in earthquake-prone regions.